The Bad Guys [videorecording (DVD)] - Blabey, Aaron (Universal, 2022)
A crackerjack criminal crew of animal outlaws are about to attempt their most challenging con yet: becoming model citizens. Never have there been five friends as infamous as these guys: dashing pickpocket Mr. Wolf, seen-it-all safecracker Mr. Snake, chill master of disguise Mr. Shark, short-fused 'muscle' Mr. Piranha, and sharp-tongued expert hacker Ms. Tarantula, aka 'Webs.' But when, after years of countless heists and being the world's most-wanted villains, the gang is finally caught, Mr. Wolf brokers a deal to save them all from prison: they will go good. Under the tutelage of their mentor Professor Marmalade, an arrogant (but adorable!) guinea pig, they set out to fool the world that they've been transformed. Along the way, though, Mr. Wolf begins to suspect that doing good for real may give him what he's always secretly longed for: acceptance. So, when a new villain threatens the city, can Mr. Wolf persuade the rest of the gang to become the Good Guys?